PENGAWASAN TENAGA KERJA ASING (TKA) DI PROVINSI RIAU - Ellen Aprilla Monica; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Migrant Workers are holders of visa for work in Indonesia. Supervisoin of migrant workers is necessary for decrease illegal workers in Pekanbaru city. Supervisoty team of migrant workers Dinas Ketenagakerjaan dan Transmigrasi Provinsi Riau, it is including relewant instantion in the implementation. The purpose of this reasearch is to know the supervision of migrant worker in Pekanbaru city. This study uses the theory of the objective use of Migrant Workers According by Manullang (2015:184) namely: Determining a Measuring Instrument (Standard), Conducting Assessment, Conducting Corrective Action. The research method is a type of qualitative research case study approach, the selection of informants using Purposive Sampling techniques. Data collection techniques through observation, interviews, and documentation. Research Results Supervision of Migrant Workers in Dinas Ketenagakerjaan dan Transmigrasi Provinsi Riau (Case Study of PT. Medco Ratch Power Riau of Project PLTGU Tenayan Raya) shows that the supervision of migrant workers activity is not yet maximal. The inhibiting factors include human resources, manye, and facilities and infrastructure. Human resources will influence supervision so that merchant participation is expected. Keywords: Supervision, Migrant Workers.